Demonstration of the use of the ICF framework in detailing complex functional deficits after major burn - Grisbrook, Tiffany; Stearne, Sarah; Reid, S.; Wood, Fiona; Rea, S.; Elliott, Catherine (Pergamon, 2012)
Burns can result in long term impairments, activity limitations and participation restrictions in a patients’ life. The focus of current surgeries and therapy is to improve body functions and structures. However, often this does not translate to an improvement in activity and participation for the patient. Improvement in activity and participation is the ultimate goal of all therapy to enhance patient’s quality of life. The incorporation of assessment measures at all levels of the International Classification of Functioning, Disability and Health (ICF) can assist in a holistic, patient centred approach to identify thecomplex impairments that impact on activity and participation, with a view to appropriately targeting future therapeutic interventions. This paper presents an example case of how implementing measures at all levels of the ICF can improve our understanding of a patient’s body functions and structures, activity and participation. A number of the outcome measures utilised in this study are novel in the burns population, such that video footage supplements the methodology where relevant.